Inquiry-Integrated STEM on Electronic Student Worksheet: An Effort to Stimulate Creative Thinking and Collaborative Skills - Anugrah, Adyt; Herlina, Kartini; Suyatna, Agus (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
This study aims to determine the practicality of developing an inquiry-based STEM-integrated electronic student worksheet to stimulate creative thinking and collaborative skills in kinetic gas theory. The electronic student worksheet was created using a development and research model adopted by Borg and Gall, and it was limited to seven steps. Data collection techniques involved direct observation, questionnaires, and surveys. The findings from this study indicate that the inquiry-based STEM-integrated electronic student worksheet is practical for learners to use in enhancing their creative thinking and collaborative skills on kinetic gas theory. Furthermore, the tests’ results categorized it as highly practical, suggesting that this electronic student worksheet can be used as teaching material to further train learners' creative thinking and collaborative skills in kinetic gas theory.